Dynamics of legal politics after Constitutional Court Decision Number 60/PUU-XXII/2024 Regarding the Party Wholesale System in the 2024 Regional Head Elections - Yudhistira, Dhieno; Nurdin, Boy (Indonesian Journal of Multidisciplinary Science, 2024)
The Constitutional Court has made a decision on regional head nominations in the Pilkada, which is an integral part of the broader general election system in Indonesia. This study analyzes the legal, political, and social implications of the decision and explores the paradigm shift in nomination, the impact on political party structures, and public reactions to these changes to create a more inclusive and participatory political climate. The study used a qualitative approach, employing a combination of legal analysis and a conceptual approach, focusing on the development and understanding of relevant legal concepts, such as democracy, political participation, and the nomination system. The results of the study suggest that lowering the nomination threshold could strengthen democracy in Indonesia by offering more opportunities for small parties and independent candidates, thereby creating an inclusive and representative election system that reflects diverse public aspirations. Moreover, the study could examine the long-term implications of these electoral reforms on political and social stability, analyzing how increased representation influences public trust in the political system.